ANALISIS MARKETING DIGITAL MELALUI SHOPEE DALAM PRESPEKTIF HUKUM EKONOMI SYARI’AH - Syukur, Musthafa; Favouritha, Amilia Mia (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The online marketing of Compass Gazelle shoes conducted by Lasker Shoop and Khasisma.Shop23 stores received a rating below 3.0 out of 5 stars when compared to Compass Store Office, which promotes similar products. This is due to the fact that the items acquired by consumers, whether in terms of size, color, or material, do not match what was advertised on YouTube and Shopee. The key differentiator between Sharia-compliant and non-Sharia-compliant transactions is the contract (akad). In Islam, promotional activities use the akad salam, so if any of the conditions between the promotion and the product do not align, the akad salam becomes void. The research method used is qualitative research. Qualitative research involves exploring and understanding the meaning from a number of individuals or groups considered to have the capacity to address the social issue being studied. The research approach used is phenomenology. The phenomenological approach is used to understand phenomena and facts in real life and social interactions. The research findings indicate that the online marketing of original Compass Gazelle shoes by Lasker Shoop and Kharisma.Shop23 does not adhere to the principles of transactions from the perspective of Sharia economics due to the presence of elements of gharar (uncertainty) and riba (usury) in its marketing, rendering the ijab-qabul or akad salam in the transaction invalid. This has led to many disappointed customers. On the other hand, the marketing of Compass Gazelle shoes at Compass Store Office aligns with the principles of transactions from the perspective of Sharia economics, and the ijab-qobul or akad salam in the transaction process is valid. This leads to sustainable success.